1999
DOI: 10.1159/000031023
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Stored Red Blood Cells for Transfusion

Abstract: Blood transfusion in a modern sense means the transfusion of red cells, when necessary supplemented by other components. The demand for plasma and plasma fractions and for platelets for therapeutic use has had an influence on the technique for preparing red cells. Automated devices have made it possible to perform collection as well as separation under more standardized conditions. Improved techniques for storage of red cells have prolonged the shelf life somewhat but most of the available methods disregard th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 55 publications
1
0
0
Order By: Relevance
“…The mean ATP values at the end of storage corresponded to 74%, 52% and 51% of initial day‐1 values for CPD, CPD/SAGM and CPD‐A1 units, respectively, and were similar to those of controls (85%, 50% and 53%, respectively). In this study, the ATP levels were comparable to those found by some workers [29,31] but slightly lower (as a percentage of initial ATP levels) than those reported by others [32,33]. They were certainly within the range of 2–3 µmol/g of haemoglobin, which is considered to be normal at the end of storage [34], and compare well to recent UK data for red‐cell storage, showing mean ATP levels of 2·49 µmol/g of haemoglobin (range: 1·74–3·24 µmol/g of haemoglobin) on day 42 [29].…”
Section: Discussionsupporting
confidence: 89%
“…The mean ATP values at the end of storage corresponded to 74%, 52% and 51% of initial day‐1 values for CPD, CPD/SAGM and CPD‐A1 units, respectively, and were similar to those of controls (85%, 50% and 53%, respectively). In this study, the ATP levels were comparable to those found by some workers [29,31] but slightly lower (as a percentage of initial ATP levels) than those reported by others [32,33]. They were certainly within the range of 2–3 µmol/g of haemoglobin, which is considered to be normal at the end of storage [34], and compare well to recent UK data for red‐cell storage, showing mean ATP levels of 2·49 µmol/g of haemoglobin (range: 1·74–3·24 µmol/g of haemoglobin) on day 42 [29].…”
Section: Discussionsupporting
confidence: 89%